Semiotic Analysis of the Pocari Sweat Ramadan Advertisement Minum Pocari Sweat Saat Sahur, IonTahanBocor Selama Berpuasa - Nurgianti, Oktavia Eka; Putra, Dhanu Ario; Diana, Eli (Jurnal Penelitian Multidisiplin Bangsa, 2026)
This research aims to analyze the types and meanings of semiotic signs found in the 2025 Ramadan edition of Pocari Sweat advertisement titled “Semiotic Analysis of the Pocari Sweat Ramadan Advertisement “Minum Pocari Sweat Saat Sahur, #IonTahanBocor Selama Berpuasa” on YouTube. This research uses a qualitative descriptive method with Charles Sanders Peirce's semiotics theory, which classifies signs into three categories, namely icons, indices, and symbols. Data were collected through observation and documentation techniques by examining scenes containing visual and verbal signs related to the advertisement's message. The analysis results show that there are 6 icon data, 9 index data, and 6 symbol data in the advertisement. Index signs are the most dominant because they show a clear cause-and-effect relationship, such as the condition of a weak body due to dehydration and recovery after drinking Pocari Sweat. These signs are used to convey an educational message about the importance of maintaining body fluids during fasting in order to stay healthy and fit. Thus, the 2025 Ramadan edition of the Pocari Sweat advertisement successfully conveys an educational message about the importance of maintaining body hydration during fasting through a combination of complementary icon, index, and symbol signs.